Study Regarding the Thickness of Fat Layer on Swine Carcasses Exploited in Semi-Intensive System - Diana Marin (Scientific Papers Animal Science and Biotechnologies, 2023)
The thickness of fat layer on the carcasses obtained from swine exploited in semi-intensive system was determined in the area: cervical, thoracic, lumbar and abdominal. In case of the first group of pigs was recorded an average of lumbar measurements of 2.2 ± 0.16 cm, of those abdominal of 1.4 ± 0.23 cm and those dorsal of 2.4 ± 0.19 cm. For the carcasses obtained through the slaughtering of the pigs from group II the average of the lumbar measurements was of 1.8 ± 0.37 cm, abdominal of 0.28 cm ± 1.1 and dorsal of 1.9 ± 0.32 cm.